Prothrombotic Effect of Anti-beta-2 Glycoprotein-1 Antibodies on the Expression of Tissue Factor, Thrombomodulin, and Plasminogen Activator Inhibitor-1 in Endothelial Cells - Rikarni Rikarni; Rahajuningsih Dharma; Tambunan L Tambunan; Harry Isbagyo; Beti E. E Dewi; Nuzirwan Acang; Rianto Setiabudy; Adi K Aman (Interna Publishing, 2015)
Aim: to analyse the effects of immunoglobulin (Ig)G and IgM anti-beta-2 glycoprotein-1 (anti-β2GP1) on the expression of tissue factor (TF), thrombomodulin (TM), and plasminogen activator inhibitor-1(PAI-1) of endothelial cells in the messenger RNA level. Methods: laboratory experimental study in human umbilical vein endothelial cells (HUVEC) was done at Cipto Mangunkusumo Hospital/Faculty of Medicine, Universitas Indonesia. Samples are purified IgG anti-β2GP1 from six  antiphospholipid syndrome (APS) patients serum and IgM anti-β2GP1 from six APS patients serum. For controls, purified IgG from six normal human serum (IgM-NHS) and purified IgM from six normal human serum (IgM-NHS) were used. HUVEC were treated with purified IgG anti-β2GP1, IgM anti-β2GP1, IgG-NHS, IgM-NHS for four hours of incubation. We measured TF, TM, and PAI-1 of HUVEC in mRNA relative expression levels (before and after treatment) by real time reverse transcription polymerase chain reaction. Results: the mean value of TF, TM, and PAI-1 mRNA levels in HUVEC after treated with IgG anti-β2GP1 compared to Ig-NHS were 3.14 (0.93)-, 0.31 (0.13)-, 5.33 (2.75)-fold respectively. In other hand, after treated with IgM anti-β2GP1 compared to IgM-NHS, mRNA levels of TF, TM, and PAI-1 were 4.33 (1.98)-, 0.33 (0.22)-, 5.47 (2.64)-fold respectively. Before and after treatment with IgG anti-β2GP1 showed significant differences of TF mRNA levels {1.09 (0.76) versus 3.14 (0.93), p=0.003}, TM mRNA levels {0.91 (0.11) versus 0.31(0.13), p=0.001}, and PAI-1 mRNA levels 0.93 (0.13) versus 5.33 (2.75), p=0.013}. Before and after treatment with IgM anti-β2GP1 showed significant differences of TF mRNA levels {1.03 (0.11) versus 4.33 (1.98), p=0.008}, TM mRNA levels {0.93 (0.08) versus 0.33 (0.22, p=0.003}, and PAI-1 mRNA levels {1.02 (0.10) versus 5.47 (2.64), p=0.01}. Conclusion: IgG anti-β2GP1 and IgM anti-β2GP1 increased TF and PAI-1 mRNA levels. However, IgG anti-β2GP1 and IgM anti-β2GP1 decreased TM mRNA levels. It proved that the mechanism of thrombosis in APS occurs through coagulation activation, reduction of fibrinolysis activity, and reduction of anticoagulant activity. Key words: APS, IgG/ IgM, anti-β2GP1, TF mRNA, TM mRNA, PAI-1 mRNA.